2020
DOI: 10.1101/2020.05.21.108373
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proliferation is a requirement for differentiation of oligodendrocyte progenitor cells during CNS remyelination

Abstract: SummaryOligodendrocytes that generate new myelin sheaths around demyelinated axons in the regenerative process of remyelination are generally derived from oligodendrocyte progenitor cells (OPCs). During this process, OPCs become activated, populate the area of myelin loss, and finally differentiate. Although much is known about the individual stages of remyelination, the exact sequence of events and whether a dependency of each individual stage on each other exists is unknown. Understanding the biology behind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The discrepancy could be attributed to the different models used in the studies, as they used mice that underwent 2 weeks of social isolation, which does not induce the loss of OPCs ( Liu et al, 2016 ). Moreover, a recent study found that in toxin-induced focal demyelination, the proliferation of the migrated OPCs is a requirement for them to differentiate at the lesion site ( Foerster et al, 2020 ). Blocking the cell cycle of OPCs in vitro resulted in a significant compromise of the differentiation of the cells ( Foerster et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discrepancy could be attributed to the different models used in the studies, as they used mice that underwent 2 weeks of social isolation, which does not induce the loss of OPCs ( Liu et al, 2016 ). Moreover, a recent study found that in toxin-induced focal demyelination, the proliferation of the migrated OPCs is a requirement for them to differentiate at the lesion site ( Foerster et al, 2020 ). Blocking the cell cycle of OPCs in vitro resulted in a significant compromise of the differentiation of the cells ( Foerster et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study found that in toxin-induced focal demyelination, the proliferation of the migrated OPCs is a requirement for them to differentiate at the lesion site ( Foerster et al, 2020 ). Blocking the cell cycle of OPCs in vitro resulted in a significant compromise of the differentiation of the cells ( Foerster et al, 2020 ). Therefore, it is possible that clemastine supports the normal cellular activities of OPCs, including proliferation and differentiation, preventing the loss of the cells rather than enhancing the cellular activities under the neurodegeneration conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Robin Franklin’s laboratory used Confetti; Sox10-iCre mice to investigate the individual response of peri-lesional OPC to focal toxin-induced demyelination. After identification of clones with hierarchical clustering analysis, the authors determined that the number and size of clones progressively increase from 3–21 days after the lesion, suggesting that many surrounding cells are responding to the lesion by repopulating it and undergoing few cycles of division [ 150 ].…”
Section: Multicolor Strategies In Pathological Contextsmentioning
confidence: 99%
“…There was a proliferative oligodendroglial response with SAG treatment in both models. Recent work has shown that increased proliferation is a prerequisite for the oligodendroglial differentiation( 31 ) and that newly generated oligodendrocytes exhibit enhanced and accurate axonal myelination( 32 ). Although we did not see a significant increase in mature CC1+ cells at these early time points, further studies are needed to determine whether SAG-induced oligodendroglial proliferation might benefit myelin generation in the long term.…”
Section: Discussionmentioning
confidence: 99%